Can a healthcare worker be a source of an infection of a patient – a risk of transmitting the chickenpox and shingles virus VZV by the staff of hospital wards – preliminary research findings. - Stryczyńska-Kazubska, Joanna; Małecka, Ilona; Biskupska, Maria; Bilski, Bartosz; Pietrzycka, Dorota; Wysocki, Jacek (Journal of Medical Science, 2017)
Introduction. Chickenpox is a highly infectious disease, caused by the Varicella-zoster virus. An infection during pregnancy poses particular risk, as it may have serious consequences for both the pregnant woman and the fetus. The only effective and safe method of preventing chickenpox is protective vaccination.Aim. This study aims to assess the risk of contracting the Varicella-zoster infection in a selected population of hospital workers, as well as the further transmission of the virus to newborns, mothers and older children.Materials and Methods. A survey was conducted in September 2014 in three public hospitals in Poznań, among nurses and midwives working in paediatric, neonatal and maternity wards. 136 nurses and midwives participated in the survey.Results. The analysis of the findings reveals that 114 staff members of the hospital wards, i.e. 83.82%, have had chickenpox in the past, 14 respondents (10.29%) have never had this illness, and 8 (5.88%) do not know if they have been ill, which means that 16% of the respondents could potentially contract chickenpox. For the majority of nurses and midwives (103) the infection had taken place before they started work. However, 11 respondents (8,08) were infected during employment.Conclusions. 1) Nearly one out of 4 hospital staff members had no history of chickenpox contraction at the beginning of their employment. 2) Nearly 15% of the workers confirm that at the beginning of employment their immunity status was established on the basis of an interview. 3) The majority of employees negatively interviewed for chickenpox history have not been recommended to be vaccinated against this disease.